Development of a standing army in 15th- and 16th-century al-Maghrib al-Aqṣā - Tomoaki Shinoda (Revue des Mondes Musulmans et de la Méditerranée)
Abstract: Researchers of the history of Morocco have been interested in the development of a standing army because they consider it as a critical factor in understanding the relationship between the state and the society in general, and the state control over the rural population in particular. In this regard, they tended to assume the discontinuity between the medieval and modern periods by stressing innovative characters of the Sharifian dynasties after the 16c in comparison to the preceding Berber dynasties. To the contrary, this paper demonstrates the continuity in the military system by examining the creation of military unit named Makhzaniyyah using sources written in Arabic and European languages. This unit was composed of elite cavalries who received a salary from taxes collected in the state treasury, defended frontier regions against attacks from enemies and controlled tribespeople in the countryside. We can confirm its existence in the armies of not only the Berber and Sharifian dynasties but also the Kingdom of Portugal who had occupied the Atlantic coasts. Its activities show that this military system was chosen as the most appropriate one for the situation of the region in this period.